The Analysis of Model for Electronic Commerce - Artificial Intelligent - Chen, Min Hui (Journal of Asian Business Strategy, 2018)
Now a day many firms has used Artificial intelligent (AI) in their ecommerce processes. Such as Apple, Amazon, Amazon and Intel use Artificial intelligent through both their services and their products, some other company using AI to help company automatic analyze customer data as well as help manager make decision. Electronic Commerce combine with Artificial Intelligent become extremely important for business in the near future. Therefore, this paper try to figure out The Analysis of Model for Electronic Commerce – Artificial Intelligent to help Business man make the best choice model in their business.